APPLICATION FOR DISSOLUTION OF LIMITED COMPANY BY THE ATTORNEY WITH THE REASON OF VIOLATION OF PUBLIC INTERESTâ€ - Dita Herlina Sari; Rahmida Erliyani; Anang Shophan Tornado (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of doing this research is to analyze first, How is the measure of violating the public interest as a reason for the attorney to dissolve a limited liability company; and secondly, what are the legal steps for a limited liability company that was filed for dissolution by the Attorney General's Office on the grounds that it violated the public interest. First Research Results because the definition of public interest is still dynamic and keeps up with the times and in UUPT does not explain the definition of public interest in detail. then the measure of violating the public interest is taken from the law which provides a definition of public interest in the Land Law, the Prosecutor's Law, the State Administrative Court Act. So that if a Limited Liability Company violates the understanding of a public interest as described in the law, the Limited Liability Company will automatically violate the Public Interest. Second: The legal steps taken are filing an objection in court on the basis that the dissolved Limited Liability Company can still carry out re-management and improve the company even better so that it can operate again in accordance with applicable regulations.